Church and society in Catholic Europe of the eighteenth century - Callahan, William James 1937-; Higgs, David 1939- (Cambridge University Press, 1979)
Of the great European institutions of the Old Regime, the Catholic Church alone survived into the modern world. The Church that emerged from the period of revolutionary upheaval, which began in 1789, and from the long process of economic and social transformation characteristic of the nineteenth century, was very different from the great baroque Church that developed following the Counter-Reformation. These studies of the Church in France, Italy, Spain, Portugal, Germane, Austria, Hungary and Poland on the eve of an era of revolutionary change assess the still intimate relationship between religion and society within the traditional European social order of the eighteenth century. The essays emphasize social function rather than theological controversy, and examine issues such as the recruitment and role of the clergy, the place of the Church in education and poor relief', the importance of popular religion, and the evangelization of a largely illiterate population by the religious orders